Teacher Strategies in Developing Students Independence in Physics Learning - Isdianti, Isdianti; Muhammad Afrialdi, Raden (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze the instructional strategies used by physics teachers to develop students’ learning independence, particularly their responsibility in completing tasks and self-confidence in solving problems, in accordance with 21st-century education demands. Methodology: This study employed a qualitative naturalistic method using direct classroom observation, in-depth interviews, and document analysis. Tools included observation checklists, interview guides, and physics learning modules. Thematic analysis was conducted using manual coding without software. Data triangulation combined teacher, student, and laboratory assistant perspectives. The subject comprised 36 tenth-grade students at State High School 11 Muaro Jambi. Main Findings: This study demonstrates that students' learning independence improves through the application of well-structured teaching strategies. Students were able to complete class assignments independently and showed strong confidence in solving physics problems. Teachers implemented inquiry-based, problem-based, and project-based learning models supported by scaffolding and contextual tasks. Activities such as group discussions, presentations, and self-reflection significantly contributed to fostering independent learning behaviors and student responsibility. Novelty/Originality of this study: The novelty of this study lies in its explicit focus on enhancing students’ learning independence through a comprehensive integration of four instructional dimensions approach, method, model, and strategy. Additionally, the inclusion of laboratory assistants as data sources enriches the contextual insight. This study contributes to the literature by illustrating how early, intentional instructional design can effectively build learning independence at the secondary school level.